Efektivitas PjBL terhadap Hasil Belajar, Berpikir Kritis, dan Motivasi Mahasiswa Teknik Elektro pada Praktikum Fisika - Winda Lestari Siregar; Annisa Tishana; Tri Isra Janwardi; Yasmiri; Teguh Wijaksana Isma; Nurul Aghnia Khairunnisa (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2026)
This study aims to analyze the effect of Project Based Learning (PjBL) on physics learning outcomes, critical thinking skills, and learning motivation among Electrical Engineering students at Universitas Malikussaleh. A quasi-experimental design with nonequivalent control group pretest-posttest was employed. The sample consisted of 60 students divided into a control group (conventional learning, n=30) and an experimental group (PjBL, n=30). Data were collected through learning achievement tests, rubric-based critical thinking instruments, and Likert-scale motivation questionnaires. It should be noted that critical thinking and motivation instruments were administered only after the treatment; therefore, pre-intervention baselines for these two variables were not measured.Shapiro-Wilk normality tests indicated non-normal distributions in several variables; therefore, the non-parametric Mann-Whitney U test was applied. Results showed: (1) the mean N-gain of the PjBL group (63.53%) was higher than the control group (26.47%); (2) critical thinking scores of the PjBL group (M=3.49; Very High category) were significantly higher than the control (M=2.72; Adequate category); (3) learning motivation of the PjBL group (M=4.45; Very High) was significantly higher than the control (M=3.16; Adequate). All Mann-Whitney U tests yielded p<0.001 with rank-biserial correlation r=1.00 and very large Cohen's d effect sizes (d=4.05–5.84). These findings provide strong evidence that PjBL was associated with higher outcomes across all three variables compared to conventional learning in the context of engineering physics practicum, although the non-randomized design limits causal claims.